PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS - Mayangsari, Lillananda Putri; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of good corporate governance and financial perfomance to the financial distress on the manufacturing companies which are listed in Indonesia Stock Exchange. The mechanism of good corporate governance in this research are i.e.: board of directors, board of commisioners, managerial ownership, institusional ownership, and the size of audit committee, meanwhile the financial perfomances in this research are profitability and leverage. The result of this research shows that the board of commissioners does not have any influence to the financial distress, the managerial ownership does not have any influence to the financial distress, the institusional ownership does not have any influence to the financial distress, the size of audit committee does not have any influence to the financial distress, leverage does not have any influence to the financial distress, the board of directors has negative influence to the financial distress, and profitabilitas has negative influence to the financial distress.Keywords: Good Corporate Governance, Profitability, Leverage, Financial Distress.